Implementasi Literasi Serta Inovasi Pemasaran Pada Usaha Mikro Kecil Dan Menengah - Deasy Wulandari; Nurhayati; Ari Subagio (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
The development of the national economy is inseparable from the rural economy because most of the people live in rural areas. When rural economic conditions are good, the national life of the people will prosper. Micro, Small and Medium Enterprises (MSMEs) are one of the drivers of supporting capability of the rural economy. The constraints of MSMEs in the rural economy are due to their location far from urban areas, so they are considered less strategic in running a business. Sukogidri Village is a village located in Ledokombo sub-district, Jember Regency. The main livelihoods of the community are farmers and “bakiak” sandal craftsmen. Marketing of MSME products from Sukogidri Village clogs still uses the traditional method, namely through local residents. This condition hampers the progress of MSMEs on a wider market scale. The findings obtained are the low level of literacy and implementation of marketing innovations for MSME. Optimizing the implementation of marketing literacy and innovation by related parties is needed to maintain business sustainability. This is done by increasing the marketing reach of MSME products to a wider market, creative and innovative approach so that they can improve the living standards of rural communities.